2013
DOI: 10.1161/strokeaha.111.000196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Unruptured Cerebral Aneurysm Therapies

Abstract: Background and Purpose-Endovascular therapy has increasingly become the most common treatment for unruptured cerebral aneurysms in the United States. We evaluated a national, multi-hospital database to examine recent utilization trends and compare periprocedural outcomes between clipping and coiling treatments of unruptured aneurysms. Methods-The Premier Perspective database was used to identify patients hospitalized between 2006 to 2011 for unruptured cerebral aneurysm who underwent clipping or coiling therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…38 From this database, morbidity rates ranging from 13.5% to 27.6% and mortality rates ranging from 0.7% to 3.5% have been reported. 2,3,4,5,6,15,18,19,22,28,41 The objective of this institutional review board-approved prospective study was to assess the feasibility and efficacy of the addition of direct neurological testing during both temporary and permanent clipping of UIAs.…”
mentioning
confidence: 99%
“…38 From this database, morbidity rates ranging from 13.5% to 27.6% and mortality rates ranging from 0.7% to 3.5% have been reported. 2,3,4,5,6,15,18,19,22,28,41 The objective of this institutional review board-approved prospective study was to assess the feasibility and efficacy of the addition of direct neurological testing during both temporary and permanent clipping of UIAs.…”
mentioning
confidence: 99%
“…These retrospective database studies have reported mortality from surgical treatment ranging from 0.7% to 3.5% and morbidity ranging from 13.5% to 27.6%. [199][200][201][202][203][204][205][206][207][208] Because of the lack of specific outcome information available in such databases, morbidity has generally been defined as discharge status to a facility other than home (including rehabilitation facilities). No longer-term outcome data past the time of discharge can be assessed, and assumptions that discharge status is a reliable surrogate for longerterm outcome are not well validated.…”
Section: Surgical Clipping Outcomesmentioning
confidence: 99%
“…2,3 Endovascular coil embolization is occasionally preferred in the management of unruptured intracranial aneurysms because it is less invasive than surgical clipping. [5][6][7][8] However, the longterm risk and durability of coil embolization are unknown. 9,10 The frequencies of aneurysm rests or recurrences are higher after coil embolization than that after surgical clipping.…”
mentioning
confidence: 99%